2022
DOI: 10.1039/d2nj00373b
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of metal oxidation states and surface acidity enhanced the trace ethylene adsorption of Ag/ZSM-5

Abstract: Trace ethylene in storage environment induces softening and ripening of fruits, causing short storage life and food wastes. Adsorption is regarded as a promising technology for the removal of trace...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Similar conclusions were drawn in a study on the selective separation of ethylene/ethane, which confirmed that separation performance is related to stable monovalent silver ions [ 16 ]. Very recently, we employed Ag/ZSM-5(130) as an adsorbent for trace ethylene removal, which achieved a capacity of 4.89 mL·g ads −1 at room temperature, primarily thanks to the π-complexation of Ag + in the adsorbent [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar conclusions were drawn in a study on the selective separation of ethylene/ethane, which confirmed that separation performance is related to stable monovalent silver ions [ 16 ]. Very recently, we employed Ag/ZSM-5(130) as an adsorbent for trace ethylene removal, which achieved a capacity of 4.89 mL·g ads −1 at room temperature, primarily thanks to the π-complexation of Ag + in the adsorbent [ 17 ].…”
Section: Introductionmentioning
confidence: 99%